Analisis Pengaruh Jumlah Tenaga Kerja Dan Investasi Terhadap TPAK Provinsi Riau - Muhammad fikry Hadi; Neng Murialti; Mizan Asnawi; Jonny Andika (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
Problems related to social conditions and employment are problems that always exist and never end. This problem is not only influenced by micro and macro factors. these side by side affect each other on the employment variable. This study uses a quantitative method, based on the philosophy of positivism which is used to look at a particular population or sample. The sampling technique was carried out randomly. data collection using research instruments. Data analysis in this study aims to test the hypotheses that have been set previously. Testing the data using Eviews 10 software using the variables of labor force participation, number of labor force, and investment.